LANGUAGE BIAS OF THE GRADE SCHOOL TEXTBOOKS BASED ON ETHNICITY - Jethro Jake C. Sampang (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study took the constructionists stance scrutinizing the language used by the grade school students in the public schools of the Division of Bataan in terms of ethnicity. Specifically, it aims to analyze the language bias present in the subjects of Social Studies (Araling Panlipunan) and Values Education (Edukasyon sa Pagpapahalaga) used by the first three grade level students in the Division of Bataan with a total of six (6) books. Each textbook was evaluated using the Critical Discourse Analysis as a research methodology to systematically analyze, describe and interpret the language used by the author that may include socio-political constructs leading to language bias. Themes such as underrepresentation of other indigenous or cultural community groups, overgeneralized description of Filipino cultural behavior, beliefs and attitudes, underrepresentation of indigenous minority groups, cultural insensitivity, misconception about indigenous or cultural community groups, discrimination against indigenous people, misconception about Filipinos, focus on low landers and inappropriate cultural terms are used to enhance the analysis of the textbooks. The findings indicate that there are excerpts that have language bias in terms of ethnicity. The researcher included proposed alternatives for the excerpts taken from the textbooks so as not to be biased in terms of ethnicity. The research highlights the importance of looking into how the language use can affect how the readers, specifically the young students, view the various ethnic groups and cultural communities.